1995
DOI: 10.1295/polymj.27.1230
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Transition Mechanisms in Poly(tetramethylene succinate)

Abstract: ABSTRACT:Poly(tetramethylene succinate) (PTMS) showed a crystal transition between the r:J. (T7 GTG) and /J (T10) form under the strain and relaxation conditions, where T, G, and G denoted trans, gauche, and minus gauche, respectively. We have investigated the mechanisms of this crystal transition by FT-IR and X-ray diffraction. In the FT-IR, the absorbance peaks at 920 cm -1 and 955 cm -1 , corresponding to the fl. form, started decreasing at strain of s 8%, while the absorbance at 977cm-1 , corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 22 publications
3
47
0
Order By: Relevance
“…Figure 6 displays WAXD patterns of PBSu, PMPSu, and PBSu-rich PBMPSu copolyesters that were isothermally crystallized at 10-12°C below their respective T m values. The unit cell of the crystalline PBSu # form is monoclinic [5][6][7][8][9], and the diffraction peaks from the (020) and (110) planes are detected at 2% ! 19.6 and 22.7°, respectively.…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 displays WAXD patterns of PBSu, PMPSu, and PBSu-rich PBMPSu copolyesters that were isothermally crystallized at 10-12°C below their respective T m values. The unit cell of the crystalline PBSu # form is monoclinic [5][6][7][8][9], and the diffraction peaks from the (020) and (110) planes are detected at 2% ! 19.6 and 22.7°, respectively.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The crystalline structure [5][6][7][8][9], and crystallization and melting behavior [10][11][12][13][14][15][16][17][18] of PBSu have been investigated extensively. PBSu has a relatively low biodegradation rate because of its high crystallization rate and high crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The crystalline structure of PBSu has been described by several authors. [10][11][12] Chatani et al [10] reported that the crystal structure of the PBSu a-form is monoclinic with unit cell dimensions a ¼ 0.521 nm, b ¼ 0.914 nm, c ¼ 1.094 nm: b ¼ 1248, P2 1 /n-C 2h . The multiple melting behavior of PBSu, mainly for samples crystallized under isothermal conditions, was also studied recently.…”
Section: Full Papermentioning
confidence: 99%
“…This new modification (b-form) has a planar zigzag conformation of all-trans T 10 and fiber repeat distance of 1.190 nm. These crystal transitions between a and b forms is reversible, and the mechanisms of the crystal transition were investigated by FT-IR and X-ray diffraction 95) . More recently, three plausible crystalline conformers with pitches (1.09, 1.16 and 1.22 nm) close to the experimental ones (1.09 and 1.19 nm) were predicted by molecular modeling by Pazur et al 55) Poly(tetramethylene adipate) (PTMA; x = 4, y = 4) crystallizes in two forms, designated as a and b forms 96) .…”
Section: Linear Aliphatic Polyestersmentioning
confidence: 99%